DUE TO LAW OF SELECTING THE RIGHT REPUDIATION CITIZENSHIP STATUS IN CITIZENSHIP LAW REVIEW OF INDONESIA - Qurrotul Uyun (Universitas Islam Balitar, 2019)
Designation (naturalization) includes giving Indonesian citizenship status of one or a number of people from foreign nationals, or gives the status as a citizen of Indonesia or the number of people who do not have citizenship (stateless) .According to the laws of the Republic of Indonesia citizens who have dual citizenship must choose one of these citizenship so until he has only one nationality. For Indonesian citizens are treated when these approvals to those Indonesian nationals, according to Indonesian citizenship legislation that called